Protective effect of N-acetylcysteine against oxygen radical-mediated coronary artery injury - Rodrigues,A.J. (2004)
The present study investigated the protective effect of N-acetylcysteine (NAC) against oxygen radical-mediated coronary artery injury. Vascular contraction and relaxation were determined in canine coronary arteries immersed in Kreb's solution (95% O2-5% CO2), incubated or not with NAC (10 mM), and exposed to free radicals (FR) generated by xanthine oxidase (100 mU/ml) plus xanthine (0.1 mM). Rings not exposed to FR or NAC were used as controls. The arteries were contracted with 2.5 µM prostaglandin F2alpha. Subsequently, concentration-response curves for acetylcholine, calcium ionophore and sodium fluoride were obtained in the presence of 20 µM indomethacin. Concentration-response curves for bradykinin, calcium ionophore, sodium nitroprusside, and pinacidil were obtained in the presence of indomethacin plus Nomega-nitro-L-arginine (0.2 mM). The oxidative stress reduced the vascular contraction of arteries not exposed to NAC (3.93 ± 3.42 g), compared to control (8.56 ± 3.16 g) and to NAC group (9.07 ± 4.0 g). Additionally, in arteries not exposed to NAC the endothelium-dependent nitric oxide (NO)-dependent relaxation promoted by acetylcholine (1 nM to 10 µM) was also reduced (maximal relaxation of 52.1 ± 43.2%), compared to control (100%) and NAC group (97.0 ± 4.3%), as well as the NO/cyclooxygenase-independent receptor-dependent relaxation provoked by bradykinin (1 nM to 10 µM; maximal relaxation of 20.0 ± 21.2%), compared to control (100%) and NAC group (70.8 ± 20.0%). The endothelium-independent relaxation elicited by sodium nitroprusside (1 nM to 1 µM) and pinacidil (1 nM to 10 µM) was not affected. In conclusion, the vascular dysfunction caused by the oxidative stress, expressed as reduction of the endothelium-dependent relaxation and of the vascular smooth muscle contraction, was prevented by NAC.